Determinación de la rentabilidad de las cajas rurales de ahorro y crédito: 2010 - 2014. - Sarachaga Horna, Carlos Miguel (2016)
This research aim to determine the factors influencing in the profitability of rural savings and credit in the period 2010-2014.The methodology used panel data with fixed effect for eight entities of rural saving and credit in the period 2010-2014, considering the hyphotesis that the market power and efficiency significantly affect profitability of rural savings and credit in the period 2010-2014. The results found in the study period show evidence for structure paradigm efficiency for rural savings and credit in the period 2010-2014. Leverage and performing loans variables also have a significant impact as determinant of profitability of rural savings and credit in the study period.